Posttraumatic stress and resilience in parents of youth with chronic pain. Issue 2 (3rd April 2019) - Khu, Melanie; Soltani, Sabine; Neville, Alexandra; Schulte, Fiona; Noel, Melanie
ABSTRACT: The objective of this study was to assess resilience in parents of youth with chronic pain, as well as to examine the relationships between parental resilience and distress, and child pain. There is evidence that parents can play a critical role in how their children's pain problems develop, are experienced, and are maintained, yet no study to date has quantitatively evaluated parental resilience. Participants were 135 parent–child dyads referred to a tertiary-level chronic pain program. Parents completed measures of post-traumatic growth (PTG), post-traumatic stress symptoms, anxiety, and depression. Youth (M age = 13.1) completed measures assessing pain intensity and interference. The most PTG was observed at moderate level of PTSS, suggesting that some stress was necessary to foster resilience. Parental PTG was positively associated with parental internalizing symptoms and child pain outcomes, and moderated the relationship between parental depressive symptoms and child pain intensity. Resilience and distress may co-exist in the parents of youth with chronic pain, with resilience acting as a potential buffer between parent distress and child pain.